2012
DOI: 10.3810/pgm.2012.07.2573
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sleep Disorders and the Risk for Developing Type 2 Diabetes Mellitus

Abstract: Sleep is increasingly being recognized as an important factor in the homeostasis of multiple body functions, including blood glucose metabolism. One of the most common sleep disorders, obstructive sleep apnea, is not only highly prevalent in patients with type 2 diabetes mellitus, but may contribute to the development of abnormalities in blood glucose metabolism. Evidence suggests that effectively treating sleep apnea, specifically with continuous positive airway pressure, improves glycemic and nonglycemic out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 92 publications
0
14
0
2
Order By: Relevance
“…Sleep is increasingly recognized as an important factor in the homeostasis of multiple body functions [19]. Many adverse health effects such as anxiety, endocrine disorders could hit the body following sleep deprivation [5], [14], [20], [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is increasingly recognized as an important factor in the homeostasis of multiple body functions [19]. Many adverse health effects such as anxiety, endocrine disorders could hit the body following sleep deprivation [5], [14], [20], [21], [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidences have shown that shift work is related with cardiovascular diseases [4,9] and type 2 diabetes [2,10] even in retired populations [11]. Some studies indicated that hypertension and type 2 diabetes were associated with metabolic syndrome (MetS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep deprivation alters glucose homeostasis, leading to insulin resistance and risk of diabetes(17, 18, 24, 59-61). Sleep extension in restricted sleepers may lessen this relationship by improving glucose tolerance(17).…”
Section: Habitual Sleep Duration and Cardiovascular Diseasementioning
confidence: 99%